Systematic analysis of human oncogenic viruses in colon cancer revealed EBV latency in lymphoid infiltrates - Fiorina, Loretta (BioMed Central, 2014)
BACKGROUND: Environmental factors may play a role in colon cancer. In this view, several studies investigated tumor samples for the presence of various viral DNA with conflicting results. FINDINGS: We undertook a systematic DNA analysis of 44 consecutive, prospectively collected primary tumor samples by real time and qualitative PCR for viruses of known or potential oncogenic role in humans, including polyomavirus (JCV, BKV, Merkel cell polyomavirus), HPV, HTLV, HHV-8 and EBV. Negative controls consisted of surgical resection margins. No evidence of genomic DNA fragments from tested virus were detected, except for EBV, which was found in a significant portion of tumors (23/44, 52%). Real-time PCR showed that EBV DNA was present at a highly variable content (median 258 copies in 10(5) cells, range 15–4837). Presence of EBV DNA had a trend to be associated with high lymphocyte infiltration (p = 0.06, χ2 test), and in situ hybridization with EBER1-2 probes revealed latency in a fraction of these lymphoid cells, with just a few scattered plasma cells positive for BZLF-1, an immediate early protein expressed during lytic replication. LMP-1 expression was undetectable by immunohistochemistry. CONCLUSIONS: These results argue against a significant involvement of the tested oncogenic viruses in established colon cancer.